Functional analysis of cag pathogenicity island diversity in helicobacter pylori isolated from multi-ethnic patients in Malaysia - Shaza Azlin Razak,; Alfizah Hanafiah,; Asif Sukri,; Neoh, Hui-Min,; Noraziah Mohamad Zin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
cagPAI is an important pathogenic marker contributing to disease severity caused by H. pylori infection, encoding proteins for type four secretion systems (T4SS) and the pro-inflammatory cytokines (IL-8) induction in infected host. The heterogeneity of cagPAI genes results in different clinical outcomes in H. pylori infection. The aim of this study was to investigate the functional diversity of cagPAI genes in clinical H. pylori strains isolated from patients with gastroduodenal diseases. Among the isolates investigated, 6 out of 27 (22.2%) harbor intact cagPAI, 3 strains (11.1%) have complete absence of cagPAI, and 18 strains (66.7%) contain a partially deleted island. IL-8 concentration is observed significantly higher among cagPAI-positive isolates (P = 0.045). Of note, IL-8 secretion in the gastric cells infected with H. pylori strains isolated from Malay patients was significantly higher than the gastric cells infected with the strains from non-Malay patients (P = 0.046). The secretion of IL-8 appears in similarly high among intact and partially deleted cagPAI isolates. East Asian cagA isolates induce a notably higher level of IL-8 than that of Western cagA. Inflammatory activities are observed and IL-8 concentration in the milder stage was found in significantly higher quantities than in the severe stage (P = 0.027). The ‘hummingbird’ phenotype was observed to cause severe effects in infected cells with cagPAI-intact H. pylori. The genetic variability of cagPAI isolates from multi-ethnicity patients may have unique implications for disease outcomes with respect to proinflammatory secretion.